The positive connection between dark triad traits and leadership levels in self- and other-ratings - Sandra Julia Diller; Andrea Czibor; Zsolt Péter Szabé; Péter Restás; Eva Jonas; Dieter Frey (Leadership, Education, Personality. An Interdisciplinary Journal, 2021)
People with high dark triad tendencies are often found in leadership positions. Yet research is lacking on whether dark triad personality traits positively correlate with the height of leadership levels (no leadership position, low-level leaders, high-level leaders, head and founder of the company). To explore this relationship between the dark triad and these leadership levels, three studies (NGermany = 137; NHungary = 333; NBothCountries = 355) were conducted, to measure dark triad scores for each leadership level. The results reveal that people in higher leadership levels display both higher self-rated and subordinate-rated dark triad scores. Further research is needed to investigate whether this finding is replicable for more objective measures and longitudinal studies as well as cultural norms, which may discourage or support dark triad traits. As the organizations are an important factor in promoting ethic-oriented behavior in individuals, one practical implication could be increased focus on developing ethical behavior during the assessment and training of leadership positions.
Keywords: 330; Dark triad; Leadership; Leadership levels; Machiavellianism; Narcissism; Psychopathy